Kinerja Aktivasi dan Impregnasi Zeolit Alam sebagai Adsorben - Sofith, Charissa Dini; Rahmadaniati Effendi, Sri; Fatimah (Talenta Publisher (Universitas Sumatera Utara), 2020)
Performance of natural zeolites can be improved through the process of activation and impregnation. Activation process using HCl and impregnation with Mg2+ have carried out in this study. The activation process was performed out for 30 minutes with a 0.5M HCl solution and impregnation of MgCl2.6H2O 2.5M for 2 hours. Natural zeolites which have been activated and impregnated are then analyzed by the Scanning Electron Microscope-Energy Dispersive Spectrophotometer (SEM-EDS). The results of zeolite surface profile characteristics activated and impregnated using SEM-EDS showed that there were changes in morphology and functional groups. Then, activated and impregnated zeolites were used to absorb ammonia at various contact times of 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes and 45 minutes. The equilibrium point was obtained at 25 minutes contact time with adsorption capacity of 30.444 mg/g and absorption efficiency of 85.2352%. The dosage of adsorbent varied with 0.01% size; 0.03%; 0.05%; 0.07%; 0.09%; 0.11%, 0.13% m/v. The concentration of ammonia absorbed was performed out using an Uv-Vis Spectrophotometer. The best efficiency of ammonia absorption is 90.106% with particle size 110-120 mesh, adsorbent dose 0.09% and adsorbent impregnation treatment.